The Legal Policy of Marriage Registration: A Dogmatic Review of the New Criminal Code Between Administrative and Criminal Law - Nur Rohim Yunus; Abbas Sofwan Matlail Fajar; Karmawan (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
Marriage registration holds a crucial position as a guarantee of certainty regarding the status of spouses and children, as well as a foundation for the integrity of population data. However, failure to register intersects with the criminal realm in the new Criminal Code. This article aims to examine whether the reporting obligation is solely administrative or, under certain circumstances, is subject to criminal sanctions under the political law of the Criminal Code. The method used is normative-dogmatic legal research with an empathetic approach: legislation to map the relationship between the Criminal Code, the Marriage Law, and population administration; the socio-juridical context to assess the barriers to access and pluralism; cases to examine the elements of action, wrongdoing, and harm; and a limited comparison with several announcements. The main findings indicate that registration is essentially an administrative obligation addressed through gradual sanctions, the obligation to verify the validity of the marriage certificate, and service integration/digitalization. Criminalization is only permitted as an ultimum remedium in cases of deception, forgery, exploitation, or actual societal harm.